Socio-religious rituals in Javanese culture: the case of traditional Ronggeng dances during the 19th and 20th centuries (2016)
The present text analyzes two cases of ronggeng, the name of dancer in the traditional tayub or tayuban dance, found in two novels: Ronggeng Dukuh Paruk, written by Ahmad Tohari, and Bawuk, written by Umar Kayam, which constitutes a small part of the Javanese culture and that is part of the cultural diversity in Indonesia. This article focuses on analyzing the socio-religious aspect in traditional Javanese dances, particularly in the case of ronggeng that was presented in the 19th century and at the beginning of the 20th century.